Material Assessment and Expert Advice on the Literacy Explanation Text Module at Medan Kudus Christian Middle School Medan, Indonesia - Perangin-angin, Esra; Solin, Mutsyuhito; Pramuniati, Isda (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
This study dealt with Material Assessment and Expert Advice on the Literacy Explanation Text Module at Medan Kudus Christian Middle School Medan, Indonesia. The type of research used is research and development or Research & Development (R and D). This research and development was put forward by Borg and Gall (Sugiyono, 2013: 298). Improvements based on the results of the assessment and advice from experts, then the learning material for writing explanatory text based on literacy after improvement contains the material understanding of explanatory text, characteristics of explanatory text, classification of explanatory texts, explanatory text structures, etc. All material will be arranged in 3 activities, activity 1: explain the definition of explanatory text, explain the characteristics of explanatory text, classify explanatory text, activity 2: examine parts of explanatory text structure, understand the language rules of explanatory texts, determine general ideas of explanatory text, summarizing the explanatory text, activity 3: determining the patterns of explanation text development, understanding the steps for writing explanatory text, writing explanatory text according to the pattern or framework that has been designed. The form of the learning material for writing literacy-based explanatory texts is packaged in size B5 with page number 84 and letter size 12. The front cover of this literacy-based explanatory text module contains the name of the supervisor, the name of the module, illustrations of book drawings and hand drawings in writing positions. For the back cover of the learning material listed a general picture of the contents of the module.